INCREASING THE EFFICIENCY OF URBAN ELECTRIC TRANSPORT USING SADT METHODOLOGY: Array - Lychov, D. (Municipal economy of cities. Series: «Economy science», 2020)
The issue of increasing the efficiency of urban electric transport through the introduction of CASE-technologies based on SADT-methodology is considered. The performance of the system analysis of the operation of urban electric transport is given. The system of urban electric transport is considered not as an isolated system that solves only its problems - making a profit, but in connection with the problems of the city, the population that uses transport services, enterprises that employ people who transport. The proposed methodology will allow to create a computer functional model of operation of electric vehicles in the IDEF0 format using the software package BPWin. It is shown that the operation of transport is a complex process consisting of three subsystems: operation management, commercial and technical operation. Each of these subsystems has its own functional tasks, which require appropriate resources. Therefore, to ensure resource conservation in the operation of rolling stock, the following levels of development are presented and considered: the city transport system, urban electric transport enterprises, technological processes of passenger transportation, maintenance, maintenance and repair of facilities and equipment. Also operation of city electric transport includes maintenance of vehicles in depot. This article describes the features of the impact of the rolling stock of urban electric transport on energy consumption, taking into account the influence of factors such as passenger cabin occupancy, mileage of the mobile unit when operating on the routes of large cities, operating speed. A new methodology for evaluating the work of a city electric transport company is presented, which allows to combine several different, economically independent enterprises into one functional model. It is shown that the use of the proposed model will make it possible to create a system of accounting for electricity consumption by different types of urban electric transport.